2015
DOI: 10.1039/c5dt02129d
|View full text |Cite
|
Sign up to set email alerts
|

Formation constants of copper(i) complexes with cysteine, penicillamine and glutathione: implications for copper speciation in the human eye

Abstract: Protonation constants for the biologically-important thioamino acids cysteine (CSH), penicillamine (PSH) and glutathione (GSH), and the formation constants of their complexes with Cu(I), have been measured at 25 C and an ionic strength of 1.00 mol dm 3 (Na)Cl using glass electrode potentiometry. The first successful characterisation of binary Cu(I)CSH and Cu(I)GSH species over the whole pH range was achieved in this study by the addition of a second thioamino acid, which prevented the precipitation that no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 66 publications
0
8
0
1
Order By: Relevance
“…Previous measurements suggest that thiols bind copper as a Cu(I) species (Leal and van den Berg, 1998;Konigsberger et al, 2015;Barman et al, 2016). From our assumption based on the correlation between thiourea-type thiols and L 1 , an important deduction from this work is that most of the copper in these coastal waters would appear to occur in the reduced form of Cu(I).…”
Section: Composition Of the Ligand Classesmentioning
confidence: 65%
See 1 more Smart Citation
“…Previous measurements suggest that thiols bind copper as a Cu(I) species (Leal and van den Berg, 1998;Konigsberger et al, 2015;Barman et al, 2016). From our assumption based on the correlation between thiourea-type thiols and L 1 , an important deduction from this work is that most of the copper in these coastal waters would appear to occur in the reduced form of Cu(I).…”
Section: Composition Of the Ligand Classesmentioning
confidence: 65%
“…As well as cell exudates, sources of thiols include pore waters (Zhang et al, 2004) and sewage effluents (Dryden et al, 2007). RSS typically form Cu(I) complexes (Leal and van den Berg, 1998;Konigsberger et al, 2015) although Cu(II)-thiolates have been generated artificially (Kitajima et al, 1990). Different thiols bind copper with a range of log K ′ CuL values, typically log K ′ CuL = 12-14 (Laglera and van den Berg, 2003) in salinities from estuarine to seawater.…”
Section: Introductionmentioning
confidence: 99%
“…Man geht davon aus, dass dies im Zusammenhang mit dem Fluss des Kammerwassers zusammenhängt [2]. Der Beginn zeigt sich i. d. R. von 10 bis 2 Uhr, breitet sich dann inferior und anschließend zirkulär aus [3]. Die Kupferpartikel infiltrieren wahrscheinlich die Descemet über das Kammerwasser durch das Endothel hindurch.…”
Section: Der Ophthalmologische Befundunclassified
“…The formation of Cu(I) complexes with cysteine was well-documented in literature. 16,17,24 In the case of D (Ia), the I-V characteristic exhibited a deviation from D (I) but without a proper resistive switching, while the devices D (Ib) and D (Ic) exhibited a resistive switching with an ON-to-OFF ratio of 5 Â 10 À2 and B10 1 , respectively. In the case of devices D (Ia) and D (Ic), the conductivity values were close to the devices made with CuP, D (I), and cysteine, D (II), respectively, due to the incorporation of low and high concentrations of cysteine into the device D (I).…”
mentioning
confidence: 99%
“…16 The formation constants of Cu-complexes with cysteine based on the thermodynamic model confirmed that a univalent copperion is predominant in blood plasma, aqueous humour and cornea of the human eye. 17 The Cu(I)-cysteine complex also acts as a hole scavenging co-catalyst that influences the activity of CdSe for hydrogen production in the presence of visible light and also minimizes the electron-hole pair recombination due to photo-excitation. 18 The translation of a chemical reaction to electrical signal generation is a well-established method in electrochemical sensing applications.…”
mentioning
confidence: 99%